Few‐Layer Antimonene by Liquid‐Phase Exfoliation - Roland Gillen (Angewandte Chemie International Edition, 2016)
We report on a fast and simple method to produce highly stable isopropanol/water (4:1) suspensions of few-layer antimonene by liquid-phase exfoliation of antimony crystals in a process that is assisted by sonication but does not require the addition of any surfactant. This straightforward method generates dispersions of few-layer antimonene suitable for on-surface isolation. Analysis by atomic force microscopy, scanning transmission electron microscopy, and electron energy loss spectroscopy confirmed the formation of high-quality few-layer antimonene nanosheets with large lateral dimensions. These nanolayers are extremely stable under ambient conditions. Their Raman signals are strongly thickness-dependent, which was rationalized by means of density functional theory calculations.